The Relationship of Self Efficacy with Assignment Skills - Ulandari Juwita; Asmidir Ilyas (Universitas Negeri Padang, 2021)
Task work skills are a skill to do tasks with various techniques and methods used. One that affects task-doing skills is self-efficacy, Sis with high self-efficacy will believe in her abilities, work on things well and don't give up on challenges, including in doing assignments. Students who actually have good skills in doing assignments, but because of low self-efficacy have an effect on the work they do. This study aims to find out the picture of student self-efficacy, the description of student task skills, and the relationship between self-efficacy and the task skills of SMA Negeri 3 Sungai Penuh students. This study used a descriptive correlational method with a total sample size of 243 selected using a proportional stratified random sampling technique. Collecting data using self-efficacy questionnaires and task skills with a Likert scale model. The results of the study revealed (1) students 'self-efficacy was in the very high category with a score of 127 and a percentage of 52.3%, (2) the students' task work skills were in the high category with a score of 155 and a percentage of 63.8%. (3) there is a significant positive relationship between self-efficacy and work skills with the Pearson correlation of 0.620 and a significant of 0.000. Thus, counseling teachers can design service programs to help students improve self-efficacy and task-doing skills for the better.